Pengembangan Modul Ajar Sejarah (IPS) Fase E Berbasis Kurikulum Merdeka: Integrasi Pengurangan Risiko Bencana (PRB) di SMAN 5 Tangerang Selatan - Jakiatin Nisa; Eko Teguh Paripurno; Yohana Noradika Maharani; Anissa Windarti; Jaka Purwanta; Arif Rianto Budi Nugroho; Eni Muryani (Universitas Hamzanwadi, 2025)
The high impact of disasters on educational institutions in Indonesia requires strengthening disaster literacy in schools. So far, the preventive aspect of disaster management has not been optimal, particularly in the development of teaching modules that are contextual and responsive to disaster risks. This study aims to develop a Phase E Grade X History Teaching Module (Social Studies) based on the Merdeka Curriculum that integrates Disaster Risk Reduction (DRR). The research uses a Research and Development (R&D) approach with a modified ADDIE model, only implementing the Analyze and Design stages. The needs analysis stage (initial analysis) was conducted through literature studies, curriculum document reviews, interviews, and observations at the Disaster-Safe Educational Unit (SPAB) of SMAN 5 South Tangerang. he results of the needs analysis indicate that the existing History Teaching Module was still conventional and had not integrated DRR. The teaching module design stage was developed by integrating DRR through changes and additions: (a) initial competencies; (b) elements to be achieved from the Pancasila Student Profile Dimensions; (c) learning objectives; (d) sparking questions before learning activities; (e) activities in the Critical Thinking Core Activity section of individual assignments; (f) questions that test students' understanding; (g) in the formative and summative assessment sections of group assignments; and (h) in enrichment and remedial activities. This PRB Integrated History Teaching Module is expected to not only improve students' understanding of disaster history, but also instill the values of preparedness and social awareness, as well as support the Disaster Safe Education Unit (SPAB) program and sustainable education goals in Indonesia.